Implementasi Algoritma Data Encryption Standard Pada Penyandian Record Database - Yanti, Neti Rusri; Alimah, Alimah; Ritonga, Desi Afrida (STIKOM Tunas Bangsa Pematangsiantar, 2018)
Record databases are generally still often displayed in text form as information for users, so it can facilitate cryptanalyst to access and provide opportunities to do the leak, distribute or modify the database records. One of the cryptographic algorithms used to secure data is using the DES algorithm to encrypt the data to be stored or sent. The DES algorithm belongs to a cryptographic system of symmetry and is a type of block cipher. DES operates on a 64-bit block size. DES describes 64 bits of plaintext to 64 bits of ciphertext using 56 bits of internal key (internal key) or up-key (subkey). The internal key is generated from an external key 64-bit length. This research describes the process of securing database records by encrypting it based on DES algorithm, resulting in text record databases in the form of passwords that are difficult to understand and understand by others. This is done in an attempt to minimize the misuse of database records.